Methodological support for effective website functioning in project-oriented architectural and construction companies - Kubanov, Ruslan; Kresan, Maksym; Makatora, Dmytro (Khmelnytskyi National University, 2026)
In the contemporary context of the development of the architectural and construction industry, a company’s website functions not only as an informational showcase but also as a multifunctional platform that ensures interactivity, transparency, and partnership dialogue among all participants in project-oriented activities. The problem lies in the fact that most companies limit themselves to a traditional approach to website development, focusing on a list of services and contact information, whereas modern trends require the creation of a collaborative ecosystem. The absence of interactive tools, feedback mechanisms, and opportunities for joint decision-making leads to informational isolation, a decline in trust, and reduced effectiveness of project implementation. The purpose of the study is to develop and substantiate the methodological foundations for creating and operating the website of an architectural and construction company as a platform for partnership dialogue, which makes it possible to transform the client from a passive consumer of information into an active co-creator of the result. The methodological framework of the research is based on the analysis of modern website development models (waterfall, spiral, Microsoft Solutions Framework, Walt Disney model), concepts of internet marketing and relationship marketing, as well as a systemic approach to considering the website as a partnership ecosystem. The study employs methods of analysis and synthesis of scientific sources, comparative analysis of models, content analysis of websites of leading Ukrainian and international companies (Archimatika, YOD Design Lab, BIG, Foster + Partners), as well as the case method to examine practical examples of integrating partnership technologies. The main results of the study consist in identifying the key directions for organizing partnership dialogue: communication transparency, interactivity, joint decision-making, systematic feedback, the use of BIM technologies, and the creation of an emotional component of interaction. Methodological recommendations regarding website structure are proposed, including the integration of client dashboards, online chats, cost calculators, multimedia materials, and localization tools for international clients. It is demonstrated that a website built on the principles of a partnership ecosystem becomes the economic foundation for company development, reduces risks, enhances communication efficiency, and fosters trust among participants in project activities. The scientific novelty of the work lies in a comprehensive approach to the methodological support of website functioning for an architectural and construction company, which combines technical models, marketing tools, and practice-oriented aspects of partnership. The practical significance consists in the possibility of using the proposed recommendations for developing websites that meet modern requirements of interactivity and transparency, as well as in shaping a new culture of communication in the field of architecture and construction. Thus, the study confirms that the website of an architectural and construction company should be considered as a platform for cooperation and dialogue, where technical structure is combined with genuine partnership, and the outcome becomes not only technical but also socio-economically significant.
Методичне забезпечення ефективності функціонування сайту в умовах проектно-орієнтованої діяльності архітектурно-будівельної компанії
Keywords: website of an architectural and construction company; project management; project-oriented activity; methodological support; partnership dialogue; interactivity; communication transparency; feedback; collaboration ecosystem; usability and content; trust and co-creation; сайт архітектурно будівельної компанії; управління проектами; проєктно орієнтована діяльність; методичне забезпечення; партнерський діалог; інтерактивність; прозорість комунікації; зворотний зв’язок; BIM технології; екосистема співпраці; юзабіліті та контент; довіра та співтворчість; економічна основа розвитку; 004.7:005.8